Writing, Filming, Building: Using a Taxonomy of Moviegoers to Appraise Spatial Imagination in Architecture - Mejía, Jorge (Writingplace, 2020)
How do we envision possible futures for the built environment? What allows us to imagine spaces that do not yet exist? While superstitious approaches to these questions often explain spatial imagination as an ineffable or arcane process, this article advances a simple description of how built space can be understood, envisioned and ultimately produced. The analytical approach developed by the writer Andrés Caicedo to explain how professional film makers approach a movie, and the differences between their approach and that of the general public, are used to illustrate how architects can also confront built space professionally, with an operative intention. Both in the film arts and in architecture, it is argued here, the technical understanding of what exists, and how it has been produced, is indispensable to imagine what might or should be. By using methods obtained from literature and cinema to illustrate the relation between architecture’s telos, or its ability to advance visions of possible futures for the built environment, and its technique, or the instruments and methods required to achieve those visions, the article makes a strong case for the utility of interdisciplinary analyses for artistic practice.